Efeito da (in)congruência de valores pessoais no relacionamento B2B - Manosso, Thayane Woellner Sviercoski (2019)
The developed study evaluated the congruence and incongruence effect between the boundary spanners’ personal values on the satisfaction and relationship value in an Agribusiness marketing channel. A dyadic perspective was adopted, having as public, the farmers attended by the sellers of machines, attachments and production inputs of the agricultural resale. For the study, the PVQ-RR of the personal values of Schwartz et al. (2012), the scale of relationship value of Alejandro et al. (2011), and the scale of satisfaction of Del Bosque Rodríguez, Agudo and San Martín Gutiérrez (2006) and Geyskens, Steenkamp and Kumar (1999) were used. The proposed hypotheses were tested using polynomial regressions with response surface analysis and the results show that congruence and incongruence have different effects, depending on the personal values and the relationship variable tested. For social focus values, both congruence and incongruence can be good to relationship value, non-economic or economic satisfaction. For personal focus values, incongruence may be better than congruence to the same variables, from the farmers’ perspective. This study contributes to the advancement of relationship marketing theory by integrating measures regarding to personal values and interorganizational relationship in a B2B market, unidentified until then in the studied theory.